PENGARUH INTANGIBLE ASSETS TERHADAP FIRM VALUE DI INDONESIA - Rennath, Monica Sharon; Wijaya, Henryanto (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study aims to find out how the role of intangible assets in the form of research and development, advertisement, and human capital on firm value in manufacturing companies listed on the Indonesia Stock Exchange during 2018-2020. The sample was selected by purposive sampling method and the valid data were 90 companies. The data processing technique used multiple regression analysis assisted by Microsoft Excel 2010 and EViews 12 Student Version Lite. The results of this study indicate that intangible assets in the form of research and development, advertisement, and human capital as well as control variables of company size and company age simultaneously or jointly have a significant effect on the dependent variable of firm value. The implication of this research is the need to increase the role of intangible assets that will increase the value of the company and attract investors to invest.